Fashion and Digital Fabrication: an emphirical investigation on the benefits of adopting digital fabrication labs as a field of study for fashion in Brazil (ModaPalavra e-periódico, 2019)
This article aim is to present part of a Phd thesis results in which an empirical research has been done in an universitary extension course. The course called “Fashion and Digital Fabrication” offered byFAU-USP Design and Architecture department in collaboration with EACH-USP's Textile and Fashion departmentin association with FabLab Casa da Memória in order to share the knowledge about how to use 3D printers and laser cutter machines within the “maker culture” but also to collect data for the before amentioned research. The main issues annalysed during the course was if it is viable and benefic to adopt practices and tools of the digital fabrication scenario, such as 3D printers and laser cutters, to be applied to the fashionfield. Also we annalized what's the level of absorption of the content by the participants, how they would like to keep using the tools in future works, which groups would benefit of this technics and which possible positive impact could it have in the brazilian contexto.
Keywords: fashion; digital fabrication; 3D print; aser cutter